Faktor-Faktor yang Mempengaruhi Keputusan Konsumen dalam Memilih Perumahan Syariah Non-Bank - Swarman, Gema Fatri; Widana, Gusti Oka (Ekonomis: Journal of Economics and Business, 2024)
This study aims to analyze the influence of Sharia PPR characteristics, knowledge, and religiosity factor on consumer decision in choosing non-bank sharia housing. This type of research is a quantitative research with descriptive method. The respondents of this study is consumers of Sharia Housing of Aster Village Ciwastra (AVC) with a total sample of 172 peoples who were selected proportionall and the data collection is using questionnaire. The verification of variables using multiple regression and the significance testing used t test (partial) and F test (simultaneous). The results of the influence test, where partially the characteristics of sharia PPR, knowledge, and religiosity factor affect consumer decision in choosing non-bank sharia housing, with the contribution of each sharia PPR characteristic of 34.37%, knowledge factor of 16.58%, and the religiosity factor is 18.02%. Simultaneously, the characteristics of sharia PPR, knowledge and religiosity affect consumer decision in choosing non-bank sharia housing, with a contribution value of 83.70%. Based on the findings, if the characteristics of sharia PPR, knowledge factor and religiosity factor are increased simultaneously, it will be followed by an increase in consumer decision to choose non-bank sharia housing.